Wisdom of the Crowd in Experiments - Senninger, Larissa Katharina (BestMasters,, 2018)
Larissa Katharina Senninger analyses the phenomenon of wisdom of the crowd in experimental capital markets. Aiming to find out which market mechanism is able to aggregate different information in a meaningful way, a continuous double auction and a call auction mechanism are tested. In line with expectations, markets with continuous double auction mechanism are better able to aggregate information and additionally take a shorter time. The author shows that receiving more information enables subjects to make better estimations, whereas more information improves the quality of estimations significantly only if it is a lot more information. Contents • Wisdom of the Crowd • Market Experiments • Information Aggregation • Experimental Capital Markets • Trading Mechanisms • Estimation of Asset Value • Call Auction Mechanism • Continuous Double Auction Mechanism Target groups • Students and lecturers in the field of economy and banking & finance • Practitioners in the banking & finance sector The author Larissa Katharina Senninger holds a master's degree from the Leopold-Franzens-University in Innsbruck. She started her professional career in the risk controlling department of a German finance service in Munich and is currently responsible for interest rate risk and liquidity risk.